The Relations and Relevances of the Poda Na Lima Batak People's Philosophy with Islamic Views - Siregar, Iskandarsyah; Demidyuk, Lyudmila (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
The essence of a nation's identity, rooted in its traditional values and philosophy, predates its establishment as a sovereign entity. This intrinsic connection to tradition shapes the foundational principles upon which the nation is built. Indonesia, like many other countries, grapples with a multitude of challenges, often encountering complexities and distortions in crafting solutions for each unique circumstance it faces. However, there exists a belief that by drawing upon the philosophical underpinnings and traditional values inherent to its culture, Indonesia can navigate and resolve these issues effectively. Central to this approach is the recognition of the pivotal role that philosophy plays in guiding societal norms and behaviours. In particular, the adoption of religious values, such as those found in Islam, holds significant promise for grounding the populace in the timeless truths encapsulated within traditional customs. Islam, characterized by its universal nature as a religion of "rahmatan lil'alamin" (mercy to all creations), offers a comprehensive framework capable of addressing various facets of human existence. This study underscores the urgency of revitalizing community life orientations, particularly among the Batak tribe, by aligning them with the principles embodied in the Poda Na Lima philosophy. By elucidating the connections between their identity as Muslims and Bataks, individuals can imbue their societal structures and infrastructure with greater resonance and authenticity. Employing a qualitative approach rooted in critical discourse analysis, this research seeks to unravel the intricate interplay between traditional philosophy, religious teachings, and contemporary challenges. Through the examination of the Poda Na Lima framework, comprising five foundational tenets, it becomes evident that these principles hold profound wisdom and serve as guiding principles for societal conduct. Moreover, the congruence between the teachings encapsulated in Poda Na Lima and Islamic doctrine reaffirms their relevance and applicability in contemporary Indonesian society. In conclusion, this study underscores the importance of integrating traditional philosophies and religious values into the fabric of national identity and governance. By leveraging these timeless principles, nations like Indonesia can navigate the complexities of modernity while remaining grounded in their cultural heritage and fostering societal cohesion and progress.